التدخل الدلالي وتأثيره في التعبير الشفهي لدى الطالبات الإندونيسيات الدارسات اللغة العربية بجامعة الراية - Na’imatun Khanifah; Evi Hulwati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
The problem that often occurs is that someone tends to carry the characteristics of the language he uses in other languages ​​when he learns and interacts with the language. This phenomenon has occurred in Indonesian students in learning Arabic at Ar Raayah University which influences the student's ta'bir syafahi. Based on this, the researcher wants to describe and analyze the forms and factors of the semantic intervention of Indonesian in Arabic from the aspects of ta'bir syafahi that occur in STIBA Ar Raayah students. This research uses descriptive analysis method based on a qualitative approach. Data collection is done by observation, interview and questionnaire techniques. The data analysis technique used is based on Miles and Huberman models. The results of this study indicate that semantic interventions have influenced the ta’bir Syafahi for STIBA Ar Raayah students, which can be seen from the use of inaccurate words in the use of Arabic or the use of Arabic words based on the meaning understood in Indonesian. This happens because of the influence of the Indonesian language, lack of knowledge about appropriate vocabulary in the use of Arabic, lack of mastery of Arabic grammar, the assumption of false and correct sentences and taklid.